Tradition in Transition Investigating the Impact of Modernization on Indigenous Cultures - Sokk, Vutthy (Journal Social Humanity Perspective, 2024)
This study explores the multifaceted impacts of modernization on indigenous cultures, focusing on the social, economic, and cultural dimensions of this complex phenomenon. Through a comprehensive examination of existing literature and case studies, we investigate the challenges and opportunities faced by indigenous communities as they navigate the forces of globalization, industrialization, and cultural homogenization. Our findings reveal profound implications for indigenous cultures, including the erosion of traditional knowledge systems and languages, the commodification of indigenous cultures, and the displacement of indigenous peoples from their traditional territories. However, amidst these challenges, indigenous communities demonstrate resilience, agency, and innovation in asserting their rights, reclaiming their cultural heritage, and advocating for sustainable development pathways.